Hubungan Sikap dalam Pencegahan Anemia dengan Status Anemia pada Remaja Putri di SMAN 1 Kartasura - Auna Najwa Salsabilla; Endang Nur Widiyaningsih (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
The results of the 2024 survey on young girls at SMAN 1 Kartasura showed that 28,03% of young girls had anemia. There are quite a lot of aspect that cause anemia, one of them refers to the attitude of students towards adherence with the consumption of blood tablets. The research goals to analyze the connection amid attitudes in the prevention of anemia also the status of anemia in adolescent girls at SMAN 1 Kartasura, Sukoharjo Regency. One of them has to do withThis utilized a cross-sectional, quantitative design. Utilizing the simple random sampling method, 83 female students made up the research sample. Data gathering was done through filling out a questionnaire to measure the respondent's attitude as well as checking hemoglobin levels using the Cyanmethemoglobin method. The attitude category is determined based on the median value, namely positive attitude (≥70,00) and negative (<70,00), while anemia status is classified into anemia (<12 g/dL) and non anemia (≥12 g/dL). According to the study's findings, 54.2% of respondents had a favourable attitude about anaemia prevention. 66.3% of people with an optimistic outlook do not suffer from anaemia. Attitude and anaemia status did not significantly correlate, according to the Chi-Square test (p=0,310). This indicates that attitude is not a aspect that directly impacts the status of anemia, because there are still other aspect that directly impact hemoglobin levels, namely the intake of nutrients both from food and supplements, tablets with blood or other supplements.